Skutki podatkowe połączenia przez przejęcie spółki osobowej przez spółkę kapitałową w podatku dochodowym - Wilk, Michał; Wirski, Jakub (Kwartalnik Prawa Podatkowego, 2016)
The Code of Commercial Companies allows companies’ mergers through transfer of all assets and liabilities of one company or partnership to another company in exchange for shares which the acquiring company issues to the shareholders or partners of the company or partnership being acquired. The aim of this paper is to determine tax consequences of such transactions, particularly in the area of income taxes. This issue is not directly regulated by the tax law.